Vertical industrial policy in the EU: An empirical analysis of the effectiveness of state aid - Jordi Gual; Sandra Jódar (EIB Papers, 2006)
This paper assesses the effectiveness of vertical industrial policies within the European Union. Vertical industrial policy is defined as government support of specific firms or industries ('picking winners' or 'supporting losers'). It is measured as state aid granted by Member States to the manufacturing sectors, with the aim to analyse to what extent this government intervention affects the growth of multifactor productivity (MFP) in manufacturing. The analysis is conducted with both sectoral and horizontal aid, since in many cases vertical aid is disguised as aid pursuing horizontal objectives. Controlling for the potential endogeneity of state aid policy, the results indicate that vertical state aid contributes positively to MFP growth.
Keywords: 330; Industriepolitik; Industriesubvention; Wirkungsanalyse; EU-Staaten